Development of e-learning application: Solar power generation - Khor, Kok Gene; Yaakob, Mazri (2015)
The purpose of this paper is to develop an E-learning application to support the use of augmented reality concept in learning process and identify the strengths and weaknesses of the application.This paper will focus on mobile learning which one of the types of e-learning is. Mobile learning is a learning technique that using the devices such as mobile phones, or tablet as a platform to carry out the learning process. The topic that had been chosen to develop and presents using the application is ―Solar Power Generation‖. In the study of this paper, some review based on literature available in the internet and library will be done to identify the problem facing in implementing blended learning system in school. Secondary data will be used in order to collect the information to the topic of this study and the process in developing the application. The concept of augmented reality will be used in developing the application, which means the topic chosen will be presented using the augmented reality concept.The application developed will be analysis based on the results and the developing process to identify its strengths and weaknesses.